PENGARUH VIRAL MARKETING, PROMOSI SOCIAL COMMERCE, DAN GAYA HIDUP TERHADAP MINAT PEMBELIAN MOBIL BEKAS BMW SERI 3 "E36" - Muhammad Ryan Firmansyah (2022)
At this 22nd century, there are tight competition between sellers that made them have to think hard to reach more buyers with more unique ways, one of which is to utilize viral marketing to raise the price of an item so the price climbs up above the market price or its fair price, by using social commerce of Facebook Marketplace to sell the stuff or service they offer. Using social commerce of Facebook Marketplace to sell stuffs that are related with lifestyle, in this instance is the BMW series 3 "E36" used car, could help sellers to reach more potential buyers easily. The population in this study are a total of 68 respondents, which consists of potential buyers and owners of BMW 3 Series "E36" used car in Jabodetabek area who utilize Facebook Marketplace to just window shopping or even bought that car. The results of smartPLS3.0 test are (1)there is a positive and significant influence of viral marketing on purchasing intention with 0.884 original sample score, (2)there is a not significant influence of social commerce promotion on purchasing intention with 0.107 original sample score, (3)there is a not significant influence of lifestyle on purchasing intention with 0.009 original sample score.